CORRELATION OF HBA1C LEVELS TO LDL, HDL AND TRIGLYCERIDE LEVELS IN TYPE 2 DIABETES MELLITUS PATIENTS IN KESUGIHAN II PUBLIC HEALTH CENTER, CILACAP DISTRICT - Lestari, Tika; Puspodewi, Dini; Farabi, Meka Faizal (Jurnal Mitra Kesehatan, 2025)
Introduction: Diabetes mellitus or DM is a disease characterized by hyperglycemia due to abnormalities in insulin secretion, insulin action, or both. To avoid complications, patients with type 2 DM with uncontrolled blood glucose levels require comprehensive treatment. Poor glycemic control results in changes in lipid profiles in type 2 DM patients. The purpose of this study was to prove the correlation of HbA1c levels with LDL, HDL, and Triglyceride levels in Type 2 DM patients at the Kesugihan II Cilacap Health Center. Methods: This study design was cross-sectional. Examination of HbA1c, LDL, HDL, and Triglyceride without comorbidities of Heart, Hypertension, and Stroke. The sample was Prolanis Type 2 DM patients who met the inclusion and exclusion criteria. The analysis used for the normality test was the Shapiro-Wilk test and the nonparametric test used the Spearman test. Results: The Spearman test results between HbA1c levels and LDL levels showed a p value = 0.216, between HbA1c levels and HDL levels showed a p value = 0.123, between HbA1c levels and triglyceride levels showed a p value = 0.326. This shows that the probability is more than 0.05. The conclusion of this study is that there is no correlation between HbA1c levels with LDL, HDL and triglyceride levels in Prolanis DM Type 2 patients at the Kesugihan II Cilacap Health Center.